Rac1 Is a Novel Regulator of Contraction-Stimulated Glucose Uptake in Skeletal Muscle - Sylow, Lykke (American Diabetes Association, 2013)
In skeletal muscle, the actin cytoskeleton-regulating GTPase, Rac1, is necessary for insulin-dependent GLUT4 translocation. Muscle contraction increases glucose transport and represents an alternative signaling pathway to insulin. Whether Rac1 is activated by muscle contraction and regulates contraction-induced glucose uptake is unknown. Therefore, we studied the effects of in vivo exercise and ex vivo muscle contractions on Rac1 signaling and its regulatory role in glucose uptake in mice and humans. Muscle Rac1-GTP binding was increased after exercise in mice (∼60–100%) and humans (∼40%), and this activation was AMP-activated protein kinase independent. Rac1 inhibition reduced contraction-stimulated glucose uptake in mouse muscle by 55% in soleus and by 20–58% in extensor digitorum longus (EDL; P < 0.01). In agreement, the contraction-stimulated increment in glucose uptake was decreased by 27% (P = 0.1) and 40% (P < 0.05) in soleus and EDL muscles, respectively, of muscle-specific inducible Rac1 knockout mice. Furthermore, depolymerization of the actin cytoskeleton decreased contraction-stimulated glucose uptake by 100% and 62% (P < 0.01) in soleus and EDL muscles, respectively. These are the first data to show that Rac1 is activated during muscle contraction in murine and human skeletal muscle and suggest that Rac1 and possibly the actin cytoskeleton are novel regulators of contraction-stimulated glucose uptake.